2013
DOI: 10.1158/1541-7786.mcr-12-0464
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Divergent Expression of Prostaglandin EP4 and EP3 Receptors in Human Prostate Cancer

Abstract: PGE2 has been implicated in prostate cancer tumorigenesis. We hypothesized that abnormal prostaglandin receptor (EPR) expression may contribute to prostate cancer growth. Twenty-six archived radical prostatectomy specimens were evaluated by immunohistochemistry (IHC) and Western blotting for the expression of EP1, EP2, EP3, and EP4. As a corollary, EPR expression in one normal (PZ-HPV7) and four prostate cancer cell lines (CA-HPV10, LNCaP, PC3, and Du145) were assessed by Western blotting. Prostate cancer and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 51 publications
1
20
0
2
Order By: Relevance
“…Consistent with these previous findings, this study as well as another recent study showed that EP3 was suppressed in prostate cancer samples compared with normal prostate samples (Huang et al 2013) and in castration-resistant cells compared with androgendependent cells. Inversely, when EP3 signaling was suppressed, LNCaP cells kept proliferating in androgendeprived conditions, similar to castration-resistant cells.…”
supporting
confidence: 93%
“…Consistent with these previous findings, this study as well as another recent study showed that EP3 was suppressed in prostate cancer samples compared with normal prostate samples (Huang et al 2013) and in castration-resistant cells compared with androgendependent cells. Inversely, when EP3 signaling was suppressed, LNCaP cells kept proliferating in androgendeprived conditions, similar to castration-resistant cells.…”
supporting
confidence: 93%
“…It has been shown that the COX-2 specific inhibitor, NS-398, and EP2 antagonist significantly suppressed migratory abilities of murine mammary tumor cells, C3L5 [38], and EP1, 2 and 4 receptor antagonists, respectively, inhibited migration of metastatic breast cancer cells, MDA-MB-231 and MCF-7 [10]. Recently, it has been also shown that PGE 2 promote migration of lung cancer cells [15], RCC [12], and prostate cancer cells [39] and that these effects are mediated through activation of EP4. In this study, we also founded that EP4 antagonist (L-161982) significantly suppressed PGE 2 -induced Caki cells migration ( Supplementary Figure 3) suggesting the pivotal role of EP4 in kidney cancer cells migration.…”
Section: Discussionmentioning
confidence: 99%
“…3.1 | PGE 2 increases RWPE-1 cell proliferation in an EP receptor antagonist-sensitive manner PGE 2 is a major downstream mediator of COX-2 that promotes cellular proliferation in PC cells (Jain et al, 2008;Jiang & Dingledine, 2013;Huang et al, 2013;Madrigal-Martínez et al, 2015;Vo et al, 2013;Wang & Klein, 2007) but its effect on the proliferation of human non-malignant prostate epithelial cells is unknown. We addressed this subject through measuring the mitochondrial reduction of MTT in RWPE-1 cells incubated with 1 µM and 10 µM PGE 2 for 24 hr.…”
Section: Resultsmentioning
confidence: 99%
“…PGE 2 can directly bind to its receptors on tumor cells to regulate cell proliferation, apoptosis, migration and invasion as well as to induce tumor cells to secrete growth factors, pro‐inflammatory mediators, and angiogenic factors that stimulate angiogenesis and local inflammation (Wang & DuBois, ). Most of these PGE 2 effects have also been specifically documented in PC cells (Huang et al, ; Jain, Chakraborty, Raja, Kale, & Kundu, ; Jiang & Dingledine, ; Madrigal‐Martínez, Lucio‐Cazaña, & Fernández‐Martínez, ; Vo et al, ; Wang & Klein, ).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation